2021
DOI: 10.1038/s41598-021-01231-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fecal and serum calprotectin in COVID-19 are not consistent with gastrointestinal symptoms

Abstract: Intestinal epithelial cell damage caused by SARS-CoV-2 infection was thought to be associated with gastrointestinal symptoms and decreased fecal consistency. The association of the gastrointestinal symptoms with the COVID-19-mediated inflammatory response triggered by the gastrointestinal immune system was investigated in this paper. Intestinal inflammation marker fecal calprotectin along with serum calprotectin and other inflammatory markers were measured in COVID-19 cases with and without GI manifestations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
(41 reference statements)
2
21
1
Order By: Relevance
“…Among these studies, only three investigated the relationship between the severity of COVID-19 and intestinal inflammation. These three studies used various definitions of disease severity with contradictory results [ 31 , 34 , 35 ]. A study in Italy demonstrated a significant correlation between elevated fecal calprotectin levels and COVID-19 disease severity, characterized by the presentation of pneumonia [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, only three investigated the relationship between the severity of COVID-19 and intestinal inflammation. These three studies used various definitions of disease severity with contradictory results [ 31 , 34 , 35 ]. A study in Italy demonstrated a significant correlation between elevated fecal calprotectin levels and COVID-19 disease severity, characterized by the presentation of pneumonia [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acute period or COVID-19, that lasts approximately four weeks [4], is driven initially by replication of SARS-CoV-2 in the cells, that seems to last longer in GI tract cells [5], and then by an exaggerated immune/inflammatory response to the virus that damages tissues [2,6], COVID-19 is a primary respiratory transmitted illness that presents with fever, fatigue, cough, shortness of breath, muscle or body aches, headache, sore throat, congestion or runny nose, loss of taste or smell, nausea, vomiting and diarrhea [7]. GI manifestations are reported in 11.4-61.1% of individuals with COVID-19 (6), and are different across the literature reviewed in frequency, presentation [8,9], onset time [10] and clinical outcome [9]. The majority of COVID-19-associated GI symptoms are mild and self-limiting.…”
Section: Introductionmentioning
confidence: 99%
“…Only interaction between SARS-CoV-2 and ACE2 receptors might be enough to disrupt the normal function of ACE2 pathway and result in diarrhea and inflammation [11] but the pathophysiology of the infection in the GI tract seems to be more complex. One study reported that fecal calprotectin (FC) and serum calprotectin (SC) might have the potency to assess the prognosis in COVID-19 patients, but increased FC and SC did not feature GI symptoms or even diarrhea in COVID-19 (9). Also, elevated FC suggested an inflammatory response in the gut, which was significantly correlated with IL-6 [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 Shokri-Afra et al also identified higher plasma and fecal calprotectin levels in COVID-19 patients when compared with healthy subjects, but no differences in patients with or without gastrointestinal symptoms. 9 Ojetti et al identified a significant association between high fecal calprotectin levels and COVID-19 pneumonia, and also disease severity. 10 With the general acceptance of the COVID-19 epidemic,it is important to identify patients at higher risk of severe disease at early clinical stages.…”
mentioning
confidence: 99%